Cell Surface Glycosylation Is Required for Efficient Mating of Haloferax volcanii - Shalev, Yarden; Turgeman-Grott, Israela; Tamir, Adi; Eichler, Jerry; Gophna, Uri (Frontiers in Microbiology, 2017)
Halophilic archaea use a fusion-based mating system for lateral gene transfer across cells, yet the molecular mechanisms involved remain unknown. Previous work implied that cell fusion involves cell-cell recognition since fusion occurs more efficiently between cells from the same species. Long believed to be restricted only to Eukarya, it is now known that cells of all three domains of life perform N-glycosylation, the covalent attachment of glycans to select target asparagine residues in proteins, and that this post-translational modification is common for archaeal cell surface proteins. Here, we show that differences in glycosylation of the Haloferax volcanii surface-layer glycoprotein, brought about either by changing medium salinity or by knocking out key glycosylation genes, reduced mating success. Thus, different glycosylation patterns are likely to underlie mating preference in halophilic archaea, contributing to speciation processes.